Multi-round QAOA and advanced mixers on a trapped-ion quantum computer. (1st January 2023) - Zhu, Yingyue; Zhang, Zewen; Sundar, Bhuvanesh; Green, Alaina M; Huerta Alderete, C; Nguyen, Nhung H; Hazzard, Kaden R A; Linke, Norbert M
Abstract: Combinatorial optimization problems on graphs have broad applications in science and engineering. The quantum approximate optimization algorithm (QAOA) is a method to solve these problems on a quantum computer by applying multiple rounds of variational circuits. However, there exist several challenges limiting the application of QAOA to real-world problems. In this paper, we demonstrate on a trapped-ion quantum computer that QAOA results improve with the number of rounds for multiple problems on several arbitrary graphs. We also demonstrate an advanced mixing Hamiltonian that allows sampling of all optimal solutions with predetermined weights. Our results are a step toward applying quantum algorithms to real-world problems.